The Effect of Posyandu Prima Health Volunteer Training on Knowledge and Attitude about Balanced Nutrition and Anthropometric Measurement Practices of Preschool Age - Hafizah Nazrah; Tetty Herta Doloksaribu (GLOBAL HEALTH SCIENCE GROUP, 2025)
Preschool age is a golden age because at this time the growth and development of children is very rapid. Posyandu Prima as a community empowerment center that provides basic health services according to the life cycle with one of the main targets being preschool-age children.This study uses a quasi experiment design with a One-Group Pre-test Pos-test design involving 15 cadres as a sample. The interventions provided were in the form of balanced nutrition education and anthropometric measurement practices through 3 meetings which included question-and-answer lectures, measurement practices, and material repetition. The data collected included knowledge, attitudes, and practices of anthropometric measurements conducted by cadres and analyzed using the Wilcoxon marked rating test to assess changes before and after the intervention.The results showed that the knowledge of cadres about balanced nutrition increased by 80% from 7.6 to 13.7, and the attitude of cadres about balanced nutrition increased by 30% from 6.6 to 8.6. The ability of cadres to practice anthropometric measurements also improved, with the weight measurement score increasing by 80% from 7.6 to 13.7.